The Influence of Human Resource Development, Job Satisfaction on Employee Performance at PVH Venlo, The Netherlands - Thenu, Agners Rosario; Hidayat, Rahmat (Journal of International Accounting, Taxation and Information Systems, 2024)
This research aims to analyze the influence of human resource development (HR) and job satisfaction on employee performance at PVH Venlo, the Netherlands. The research method used was a questionnaire survey distributed to 90 PVH Venlo employees. The data was then analyzed using structural equation modeling with partial least squares. SEM was chosen because it is more accurate in processing data, not only to obtain causality between variables and constructs but also to determine the magnitude of the relationship between variables and constructs. The research results show that HR development has a positive and significant influence on employee performance. Apart from that, job satisfaction was also found to have a significant influence on employee performance. The combination of an effective HR development program and a high level of job satisfaction contributes significantly to improving employee performance at PVH Venlo. These findings underscore the importance of investing in human resource development and increasing job satisfaction as key strategies for improving organizational performance. This research provides practical implications for PVH Venlo management to continue optimizing HR development programs and creating a work environment that supports employee satisfaction.